Efficacy of the Couples’ Relationship Enrichment Training According to Choice Theory on the Psychological Resilience and Affective Divorce of Couples with Marital Conflicts - Razieh Sodagar; Alireza Maredpour; Khosro Ramazani (پژوهش‌های کاربردی روانشناختی)
The purpose of the current study was to investigate the effectiveness of the couples’ relationship enrichment training, as per choice theory, in terms of the psychological resilience and affective divorce of couples experiencing marital conflicts. The research method was quasi-experimental, utilizing a pretest, posttest, and two-month follow-up period. The statistical population of the current research consisted of couples with marital conflicts who visited six consultation centers in zone eight in Shiraz during the autumn and winter of 2020. 35 couples were randomly assigned to the experimental and control groups (17 couples in the experimental group and 18 in the control group), using the multi-stage sampling method. During a period of two and a half months, the experimental groups were provided with ten sessions of couples’ relationship enrichment training that was based on choice theory. Marital Conflict Questionnaire (MCQ), Psychological Resilience Questionnaire (RQ), and Emotional Divorce Scale (EDS). The data were analyzed through mixed ANOVA via SPSS23 software. the couples’ relationship enrichment theory, which is based on choice theory, has significant effect on the psychological resilience (F=80.28; Eta=0.54; p<0.001) and affective divorce (F=59.95; Eta=0.47; p<0.001) of couples experiencing marital conflicts. According to the findings, the couples’ relationship enrichment training, which is based on choice theory, can be a highly effective approach to enhance psychological resilience and reduce affective divorce in couples with marital conflicts. This is achieved by recognizing needs, training responsible behavior, establishing realistic plans, and investigating options and alternative selections.